Melanoma in children and adolescents: analysis of susceptibility genes in 123 Italian patients. (3rd November 2021) - Pellegrini, C.; Raimondi, S.; Di Nardo, L.; Ghiorzo, P.; Menin, C.; Manganoni, M.A.; Palmieri, G.; Guida, G.; Quaglino, P.; Stanganelli, I.; Massi, D.; Pastorino, L.; et al.
Abstract: Background: A polygenic inheritance involving high, medium and low penetrance genes has been suggested for melanoma susceptibility in adults, but genetic information is scarce for paediatric patients. Objective: We aim to analyse the major high and intermediate melanoma risk genes, CDKN2A, CDK4, POT1, MITF and MC1R, in a large multicentre cohort of Italian children and adolescents in order to explore the genetic context of paediatric melanoma and to reveal potential differences in heritability between children and adolescents. Methods: One‐hundred‐twenty‐three patients (<21 years) from nine Italian centres were analysed for the CDKN2A, CDK4, POT1, MITF, and MC1R melanoma predisposing genes. The rate of gene variants was compared between sporadic, familial and multiple melanoma patients and between children and adolescents, and their association with clinico‐pathological characteristics was evaluated. Results: Most patients carried MC1R variants (67%), while CDKN2A pathogenic variants were found in 9% of the cases, the MITF E318K in 2% of patients and none carried CDK4 or the POT1 S270N pathogenic variant. Sporadic melanoma patients significantly differed from familial and multiple cases for the young age at diagnosis, infrequent red hair colour, low number of nevi, low frequency of CDKN2A pathogenic variants and of the MC1R R160W variant. Melanoma in children (≤12 years) had more frequently spitzoid histotype, were located on the head/neck and upper limbs and had higher Breslow thickness. The MC1R V92M variant was more common in children than in adolescents. CDKN2A common polymorphisms and MC1R variants were associated with a high number of nevi. Conclusion: Our results confirm the scarce involvement of the major high‐risk susceptibility genes in paediatric melanoma and suggest the implication of MC1R gene variants especially in the children population. Abstract : Linked Commentary: H. Helgadottir. J Eur Acad Dermatol Venereol 2022; 36 : 167–168. https://doi.org/10.1111/jdv.17879 .